The β-adrenergic receptor-SGK1 signaling pathway in brown adipocytes protects GOT1 from proteasomal degradation - Park, Chul-Hong; Park, Minsung; Collier, J. Jason; Chang, Ji Suk (Frontiers in Cell and Developmental Biology, 2025)
The malate-aspartate shuttle (MAS) is a key biochemical system that facilitates the transfer of reducing equivalents from the cytosol into mitochondria. It consists of two pairs of cytosolic and mitochondrial enzymes: glutamic-oxaloacetic transaminases (cGOT1, mGOT2) and malate dehydrogenases (cMDH1, mMDH2). We recently reported that cytosolic GOT1 is selectively elevated in brown adipocytes during cold exposure, while the expression of other MAS enzymes remains unchanged. Mechanistically, cold-induced activation of the β-adrenergic receptor (βAR)-cAMP-PKA signaling pathway promotes Got1 transcription through the transcriptional coactivators PGC-1α and NT-PGC-1α. The resulting increase in GOT1 levels activates the MAS, thereby supporting mitochondrial respiration through enhanced fatty acid oxidation. In the present study, we identify the βAR-SGK1 (Serum- and Glucocorticoid-inducible Kinase 1) signaling axis as a novel regulatory mechanism that maintains GOT1 protein stability. SGK1 is activated downstream of βAR signaling in brown adipocytes during cold exposure. We show that expression of SGK1S422D, a constitutively active form of SGK1, protects GOT1 from ubiquitination by the E3 ubiquitin ligase RNF34 and subsequent degradation by the proteasome. Conversely, both pharmacological and genetic inhibition of SGK1 during βAR stimulation leads to a reduction in GOT1 protein levels without altering its mRNA expression. Together, these findings uncover a previously unrecognized role for the βAR-SGK1 signaling pathway in maintaining GOT1 protein stability in brown adipocytes, highlighting a multilayered signaling network that orchestrates metabolic adaptation during cold-induced activation.